FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN MENJALANI REHABILITASI PASIEN PASCA STROKE DI POLIKLINIK NEUROLOGI RSUD LABUANG BAJI MAKASSAR - Rusli Taher (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
Objective: The objective of this study was to look at factors related to adherence to rehabilitation of post-stroke patients at the Neurology Polyclinic of Labuang Baji Hospital in Makassar. Method: In this study used the research design used in this study is cross sectional that researchers do observation or measurement of variables at one time. The sample size in this study are 30 respondents who match the inclusion criteria. The data were collected by using questionnaires. Results: The results showed that there was a relationship between sex and rehabilitation adherence (p = 0.029), there was a correlation between education and adherence to rehabilitation (p = 0,000), there was a relationship between socio-culture and rehabilitation compliance (p = 0.049) motivation with rehabilitation adherence (p = 0.030), and there was a relationship between family support and adherence to rehabilitation (p = 0.013). Conclusion: The conclusion in this study is that there is a relationship between sex, education, social culture, motivation and family support with rehabilitation compliance. Suggestion: The results of this study can provide input for the nursing service unit, especially knowledge of factors related to adherence to rehabilitate post-stroke patients